iNKT and MAIT Cell Alterations in Diabetes - Magalhaes, Isabelle; Kiaf, Badr; Lehuen, Agnès (Frontiers in Immunology, 2015)
T1D and T2D are multifactorial diseases with different etiologies in which chronic inflammation takes place. Defects in iNKT cell populations have been reported in both T1D and T2D patients, mouse models and our recent study revealed MAIT cell defects in T2D and obese patients. Regarding iNKT cells many studies in NOD mice demonstrated their protective role against T1D whereas their potential role in human T1D is still under debate. Studies in mouse models and patients suggest that iNKT cells present in adipose tissue could exert a regulatory role against obesity and associated metabolic disorders such as T2D. Scarce data is yet available on MAIT cells, however we recently described MAIT cell abnormalities in the blood and adipose tissues from obese and T2D patients. This data show that a link between MAIT cells and metabolic disorders pave the way for further investigations on MAIT cells in T1D and T2D in humans and mice. Furthermore, we hypothesize that the gut microbiota alterations associated with T1D and T2D could modulate iNKT and MAIT cell frequency and functions. The potential role of iNKT and MAIT cells in the regulation of metabolic pathways and their crosstalk with microbiota represent exciting new lines of research.